PENGEMBANGAN ASESMEN PEMBELAJARAN SESUAI TUNTUTAN KURIKULUM 2013 PADA MATERI FOTOSINTESIS DI SMP - Siti Sriyati; Eneng Rahmayanti (Universitas Sebelas Maret, 2014)
Curriculum 2013 provides the consequences of learning assessment. Assessment claimed is authentic assessment, which includes an assessment of attitudes, knowledge and performance / skills . The purpose of this study was to develop an appropriate assessment 2013 curriculum demands on materials of photosynthesis in junior class 8 . Expansion assessment performed on practical learning method Ingenhouz experiment . Assessment developed include: questions of science process skills (SPS) and the Student Worksheet (SWS) to measure the results of studying the nature of cognitive , attitude assessment for learning to measure the results of studying the nature of affective and observation procedures used to measure the results of studying the nature psychomotor . Developed Assessment tried in undergraduate students of junior high school1 Jatinangor 1 class with a total of 36 students . The results showed that the form of the questions assessment SPS and the questions at SWS may disclose the ability of students in observing , communicating , interpretation , applying the concepts and the ability to use tools and materials .. Whereas assessment developed performance can reveal the ability of students in experiment Ingenhouz and demonstrate the process of photosynthesis to produce starch . Assessment to measure attitudes may reveal an attitude of curiosity , thorough, honest , and careful attitude of the students. Keywords: Expansion assessment , assessment authentic , attitude assessment , evaluation knowledge , skills assessment